Using the capabilities approach for strengthening the sense of professionalism of teachers deeming themselves surveilled through a Panopticon - Potgieter, F.J.; Van der Walt, J.L.; Wolhuter, C.C. (The IIE, 2016)
According to some teachers practising their profession in some of the most advanced and privileged schools in widely different parts of South Africa, they are not allowed by their superiors to work (optimally) as professionals. As a first step towards searching for a solution to this problem, we consider whether Jeremy Bentham’s and Foucault’s Panopticon metaphor might not explain the problem in greater depth. Based on our conclusion that the metaphor, having been developed initially as a solution to the problem of improving supervision and surveillance in penitentiaries, does not seem to typify fully the situation that some teachers are experiencing in their schools, we attempt to address the problem by suggesting to school managements to draw on the capabilities theory of Nussbaum, Sen and others for strengthening teachers’ sense of professionalism.
Keywords: Panopticon; Capabilities theory; Teachers; Professionalism